THE EFFECT OF PROFITABILITY, LIQUIDITY, CAPITAL STRUCTURE, AND MANAGERIAL OWNERSHIP ON DIVIDEND POLICY IN MANUFACTURING COMPANIES LISTED ON THE IDX - Fittriana (PT. Radja Intercontinental Publishing, 2025)
This research aims to examine and analyze the influence of Return on Equity (ROE), Current Ratio (CR), Debt to Equity Ratio (DER), and Managerial Ownership (MOWN) on the Dividend Payout Ratio (DPR) in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2011–2014 period. The population of this study consists of all publicly listed manufacturing companies. The sample was selected using a purposive sampling method, resulting in 11 companies that met the specified criteria. The study employs multiple linear regression analysis, complemented by t-tests and F-tests, and the data were processed using EViews 8. This is a quantitative study that utilizes secondary data, collected through the documentation of annual financial statements of manufacturing companies listed on the IDX. The results show that, partially, Return on Equity has a positive and significant effect on the Dividend Payout Ratio. The Current Ratio has a negative and significant effect, while the Debt to Equity Ratio has a negative but insignificant effect. Managerial Ownership has a negative and significant effect on the Dividend Payout Ratio. Meanwhile, when tested simultaneously, ROE, CR, DER, and MOWN have a positive and significant effect on the Dividend Payout Ratio.